Elaboration of a benzofuran scaffold and evaluation of binding affinity and inhibition of Escherichia coli DsbA: A fragment-based drug design approach to novel antivirulence compounds. (1st September 2021) - Duncan, Luke F.; Wang, Geqing; Ilyichova, Olga V.; Dhouib, Rabeb; Totsika, Makrina; Scanlon, Martin J.; Heras, Begoña; Abbott, Belinda M.
Graphical abstract: Abstract: Bacterial thiol-disulfide oxidoreductase DsbA is essential for bacterial virulence factor assembly and has been identified as a viable antivirulence target. Herein, we report a structure-based elaboration of a benzofuran hit that bound to the active site groove of Escherichia coli DsbA. Substituted phenyl groups were installed at the 5- and 6-position of the benzofuran using Suzuki-Miyaura coupling. HSQC NMR titration experiments showed dissociation constants of this series in the high µM to low mM range and X-ray crystallography produced three co-structures, showing binding in the hydrophobic groove, comparable with that of the previously reported benzofurans. The 6-( m -methoxy)phenyl analogue (2b ), which showed a promising binding pose, was chosen for elaboration from the C-2 position. The 2, 6-disubstituted analogues bound to the hydrophobic region of the binding groove and the C-2 groups extended into the more polar, previously un-probed, region of the binding groove. Biochemical analysis of the 2, 6-disubsituted analogues showed they inhibited DsbA oxidation activity in vitro . The results indicate the potential to develop the elaborated benzofuran series into a novel class of antivirulence compounds.